Power spectra of large-scale disturbances of the Indian southwest monsoon (MAUSAM, 1973)
The period, wavelength and vertical structure of the different types of monsoon disturbances have been studied by applying the technique of power and cross spectrum analysis to wind data over the Indian region.The spectra of the meridional component of wind show dominant peaks around 15-20 days and 5'-6 days in the lower troposphere and 7-9 days in the middle and upper tropospheres, These as shown to correspond to known monsoon disturbances.